An Experimental Investigation on Rehabilitation of RC Beams Using CFRP Sheets - P Rajalekshmi, Dr.J Prakash Arul Jose (International Journal of Advanced Science and Technology, 2020)
One of the most difficult challenges that engineers face today is the repair and retrofitting of concrete structures. This work consisted of measuring four rectangular beams to assess the effect of externally U-shaped bonded FRP sheets over the entire beam length on the specific reinforcement scheme. In the laboratory a total of four reinforced concrete beams with different CFRP configurations were developed for the strengthening purposes. First beam known as Control Beam (CB1) was not bonded with FRP sheets, and three other beams (FSB 1, FSB 2, FSB 3) were bonded to various FRP sheet layers (1,2 and 3 layers respectively). It was found that the experimental tests showed the better results in strength with respect to the layers of CFRP sheets.